2017
DOI: 10.1111/bph.13906
|View full text |Cite
|
Sign up to set email alerts
|

Recent advances in the development of T‐type calcium channel blockers for pain intervention

Abstract: This article is part of a themed section on Recent Advances in Targeting Ion Channels to Treat Chronic Pain. To view the other articles in this section visit http://onlinelibrary.wiley.com/doi/10.1111/bph.v175.12/issuetoc.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
91
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 102 publications
(93 citation statements)
references
References 83 publications
(99 reference statements)
1
91
0
1
Order By: Relevance
“…In neurons, T‐type channels activate near resting membrane potentials where they contribute to action potential firing thresholds and bursting frequencies and are implicated in pathophysiologies such as generalized seizures and pain transmission . A number of lines of evidence have indicated that the Cav3.2 isoform selectively contributes to somatic and visceral nociceptive pain and that inhibition of Cav3.2 channel currents attenuates nociception in a variety of animal neuropathic pain models . Here, we found that consistent with the current decrease induced by melatonin, activation of MT 2 receptor in small TG neurons led to a decrease in excitability; an effect abolished by PKC η ‐shRNA and direct T‐type channel blockade.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…In neurons, T‐type channels activate near resting membrane potentials where they contribute to action potential firing thresholds and bursting frequencies and are implicated in pathophysiologies such as generalized seizures and pain transmission . A number of lines of evidence have indicated that the Cav3.2 isoform selectively contributes to somatic and visceral nociceptive pain and that inhibition of Cav3.2 channel currents attenuates nociception in a variety of animal neuropathic pain models . Here, we found that consistent with the current decrease induced by melatonin, activation of MT 2 receptor in small TG neurons led to a decrease in excitability; an effect abolished by PKC η ‐shRNA and direct T‐type channel blockade.…”
Section: Discussionsupporting
confidence: 81%
“…Three genes encoding T‐type channels, Cav3.1, Cav3.2, and Cav3.3, are differentially and widely expressed in brain and peripherally . Aberrant T‐type channel function is associated with pathological conditions such as slow‐wave sleep, the absence of epilepsy, and pain perception . In addition, as evidenced by genetic, pharmacological, and functional analyses, specific T‐type channel isoforms both facilitate and amplify peripheral pain signaling.…”
Section: Introductionmentioning
confidence: 99%
“…Some of these substances have not yet been tested in the clinic, whereas others have yielded Gagnon et al, 2013 KYS05090S or ABT-639. . Small-molecule T-channel blockers Jarvis et al, 2014;Zhang et al, 2015a;M'Dahoma et al, 2016 N-((1-(2-(tertbutylamino)-2-oxoethyl)piperidin-4-yl)methyl)-9-pentyl-9Hcarbazole-3-carboxamide CB2 agonist that targets Ca v 3.2 T-type channels Berger et al, 2014;Bladen et al, 2015;Snutch and Zamponi, 2017 A-1264087 State-dependent Ca v 2 blockers Oral administration of all of these drugs displays antiallodynic efficacy in rodent models (Patel et al, 2017) Under development Zamponi et al, 2015 Coull et al (2003) showed that a decrease in transmembrane chloride gradient occurred in rat dorsal horn lamina I neurons following peripheral nerve injury as a result of a reduction in expression of the potassium-chloride exporter, potassium-chloride exporter 2 (KCC2). The resulting accumulation of intracellular Cl 2 can cause normally inhibitory GABAergic, anionic, outward synaptic currents to become inward excitatory currents (Coull et al, 2003;Prescott et al, 2006).…”
Section: A Excitation-inhibition Balance In Neuropathic Painmentioning
confidence: 99%
“…In addition to the established role of changes in N-type Ca 2+ channels, certain lines of evidence support an additional contribution of L-type Ca 2+ channels in the maintenance of neuropathic pain (Balasubramanyan and Smith, 2005;Fossat et al, 2010;Chang et al, 2015;Radwani et al, 2016). This has led to increased interest in broad-spectrum dihydropyridine-related Ca 2+ channel blockers such as M4, which blocks Ca v 1.2 (L-type), Ca v 2.2 (N-type), and Ca v 3.2 and 3.3 (T-type channels) Zamponi et al, 2015 Snutch and Zamponi, 2017). This is especially the case as T-type Ca 2+ channel currents are increased in sensory neurons following nerve injury in a model of diabetic neuropathy (Jagodic et al, 2007(Jagodic et al, , 2008.…”
Section: Role Of Ectopic Activity In Primary Afferent Fibersmentioning
confidence: 99%
See 1 more Smart Citation